Wind Generation, Power System Operation and Emissions Reduction - Denny, Eleanor (My University, 2006)
With increasing concern over global climate change, policy makers are promoting renewable energy sources, predominantly wind generation, as a means of meeting emissions reduction targets. Although wind generation does not itself produce any harmful emissions, its effect on power system operation can actually cause an increase in the emissions of conventional plants. A dispatch model was developed which analyses the impact that wind generation has on the operation of conventional plants and the resulting emissions of Carbon Dioxide (CO2), Sulphur Dioxide (SO2) and Oxides of Nitrogen (NOX). The analysis concentrates on a 'forecasted? approach which incorporates wind generation forecasts in the dispatch decisions. It was found that wind generation could be used as a tool for reducing CO2 emissions but alone it was not effective in curbing SO2 and NOX emissions.
PUBLISHED
Keywords: Wind generation; Emissions; Power system operation; Energy; Generation